INCLUSIVE EDUCATION AND ITS CHALLENGES TODAY - Silva, Marineide de Alhuquerque (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2026)
Inclusive education has become a reality full of challenges and opportunities for educational institutions. The objective of this article is to analyze the challenges and opportunities that arise in school institutions related to inclusive education. Inclusive education has its antecedent in special education, this definition is widely accepted and explicit in educational compendiums in Brazil, relating to other pedagogical traditions, in which the defense of school and public education is supported. However, it is important to note that inclusion as such not only encompasses the educational scope, but also encompasses the social problem that this represents in the entire school community. In view of this, the present work aimed to analyze these aspects in the bibliographic and literary context today.